Hide and seek - Patterson, James (London HarperCollinsPublishers, 1997)
Maggie Bradford is on trial for murder. One of the best-loved singer/songwriters anywhere, she seems to have it all. And so, the world wants to know, how could she have murdered not just one, but two of her husbands? This thriller comes from the author of "Along Came a Spider" and "Kiss the Girls
1
Keywords: English Fiction